TRANSLATING COMIC: AN ALTERNATIVE FOR CLASSROOM ACTIVITY - Ikawati, Tasrikha (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
The teaching of English in secondary level is based on genre approach. Comic as one of narrative text provides the possibility to be explored in translation activities. Translation process is employed as a mean to enhance the students’ skills in English, not merely to get perfect final product. The classroom activities are planned in such a way to avoid excessive linguistic and vocabulary concern which prevent the class from communicative activities.